Pemanfaatan Teknologi Pengering Sistem Aliran Silang (Cross Flow) Untuk Meningkatkan Kecepatan Produksi Pembuatan Dodol Nangka - I K. Wiratama; A. D. Catur; I.D. K. Okariawan; I. W. Joniarta (JURNAL KARYA PENGABDIAN, 2019)
Processing dodol jackfruit in the village Suranadi still use the traditional way so that the speed and quality of production is very dependent on the weather conditions. Until now there is no making of dodol jackfruit that utilize the dryer technology in the production process when many problems of production such as product quality and production speed is very low. To solve the problem, the intervention of the use of dryer technology into the production system and its management repair. From the results of the activities based on design modification then with the new system using only 1300 watts power. The thermostat is in the temperature of 900C with a drying time of 10 hours then the dryer is able to dry the dodol weighing 45 kg. This indicates that production constraints can already be resolved. With wet dodol for Rp 30,000/kg then with this tool dry Dodol can be sold at the price of Rp 45,000/kg. Production costs can also be reduced where the old dryers are needed 2300 watts of power while the tool requires only 1300 watts of power.